Experimental and numerical study on choosing proper pulse shapers for testing concrete specimens by split Hopkinson pressure bar apparatus. (30th October 2016) - Bagher Shemirani, Alireza; Naghdabadi, R.; Ashrafi, M.J.
Highlights: Using a proper pulse shaper is prerequisite for valid SHPB tests of concrete specimens. Numerical results validated by SHPB tests are used to provide guidelines to choose pulse shapers. Cross sectional area and thickness of pulse shaper is proportional to the striker bar velocity. Relatively small diameter and thick pulse shaper is recommended as proper one for concrete specimens. Abstract: Dynamic behavior of concrete specimens is investigated experimentally and numerically by split Hopkinson pressure bar (SHPB) tests. In order to accurately determine dynamic properties of brittle materials such as concrete, specimens should be subjected to particular pulse loading that can be generated by using pulse shapers. Choosing proper pulse shaper dimensions helps to obtain dynamic stress equilibrium, achieve constant strain rate and minimize pulse oscillation in the concrete specimens. To this end, SHPB tests are performed for concrete specimens and effective parameters on shaping pulses such as striker bar velocity, diameter and thickness of the pulse shaper are studied experimentally and numerically. In this regard, dynamic compressive strength, modulus of elasticity, toughness and damage behavior of the concrete specimens are calculated incorrectly if improper pulse shaper is used. Numerical results validated by the experimental data are used to provide general guidelines to properly choose dimensions of the pulse shapers for the concrete specimens in the SHPB test. Results show that use of a relatively small diameter and thick pulse shaper is suggested as a proper one for testing concrete specimens. Based on the findings of this research, if a proper pulse shaper is available for testing the concrete specimen in a specified strain rate, for other strain rates the cross sectional area as well as thickness of the pulse shaper should be changed proportional to the striker bar velocity that is related to the strain rate in the specimen.